Does CEFR (Common European Framework of Reference) fit the expectation: Voices from the classroom - Khairunnisa Dwinalida; Muflihah; Bunga Putri Maulia (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2024)
The CEFR, known globally as a key framework for structuring English language curricula, has been adopted in many educational systems worldwide. However, despite its widespread recognition, its practical application within Indonesian universities has not gained the same level of traction, remaining relatively limited compared to other regions. This difference has attracted scholarly interest, leading to research exploring the framework's applicability and potential adaptation. The research investigated how students view the fit between the framework and their expectations of the competencies of English teacher training graduates. To gather numerical data on students’ perceptions, a targeted sample of 94 participants completed a questionnaire developed based on C1-level CEFR descriptors. Complementing the quantitative data, semi-structured interviews were conducted with a subset of respondents to gather richer qualitative insights into their perceptions. Analysis of the quantitative data, including calculating the average score, showed a generally positive student perception of CEFR, with an average score of 3.78. Qualitative analysis of the interview data identified four key reasons for student agreement with the CEFR descriptors: alignment with job requirements, usefulness as communication tools, the reflection of the community expectations, and potential to support their learning. The findings imply that the stakeholders must specify the curriculum framework in which CEFR adoption can be an option. Based on these findings, it is implied that stakeholders responsible for curriculum development should specify a clearly defined framework within which CEFR adoption can be effectively implemented.